Regular Exercise Modifies Histopathological Outcomes of Pharmacological Treatment in Experimental Autoimmune Encephalomyelitis - Bernardes, Danielle; Oliveira, Alexandre Leite Rodrigues de (Frontiers in Neurology, 2018)
Background: Although it has been suggested that healthier lifestyle may optimize effects of the immunomodulation drugs for treating multiple sclerosis (MS), the knowledge regarding this kind of interactions is limited. Objective: The aim of the present study was to investigate the effects of treadmill exercise in combination with pharmacological treatment in an animal model for MS. Methods: C57BL/6J female mice were subjected to daily treadmill exercise for 4 weeks before immunization and 6 weeks before clinical presentation of disease. Dimethyl fumarate (DMF) or glatiramer acetate (GA) were administered after the first clinical relapse. Histopathological analyses were carried out in the lumbar spinal cord at peak disease and at 1 or 14 days post-treatment (dpt). Results: Exercised-GA treated animals demonstrated decreased astrocytic response in the spinal dorsal horn with an improvement in the paw print pressure. Exercised-DMF treated animals showed an increased microglial/macrophage response on both ventral and dorsal horn that were associated with clinical improvement and synaptic motoneuron inputs density. Conclusion: The present data suggest that prior regular exercise can modify the effects of pharmacological treatment administered after the first relapse in a murine model for MS.